If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -7 = 9x + -19 Reorder the terms: -7 + 6x = 9x + -19 Reorder the terms: -7 + 6x = -19 + 9x Solving -7 + 6x = -19 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -7 + 6x + -9x = -19 + 9x + -9x Combine like terms: 6x + -9x = -3x -7 + -3x = -19 + 9x + -9x Combine like terms: 9x + -9x = 0 -7 + -3x = -19 + 0 -7 + -3x = -19 Add '7' to each side of the equation. -7 + 7 + -3x = -19 + 7 Combine like terms: -7 + 7 = 0 0 + -3x = -19 + 7 -3x = -19 + 7 Combine like terms: -19 + 7 = -12 -3x = -12 Divide each side by '-3'. x = 4 Simplifying x = 4
| -540+(-13.40x)=1500 | | 3(8+7x)=24-x | | 12a+6b-36= | | 7y-45=95 | | 2x^2+6x+8=224 | | y=3x^2-8x+1 | | C-3=-12 | | 280=(18-x)(x)+(20x) | | 60=3x+9 | | 6x^2-11-60=0 | | -540+13.40x=1500 | | -1.6x^2+3.2x+18=0 | | 3/6=1x | | -1.6x^2+3.2x=-18 | | 11-4x=7(-7+6x) | | 12(10)4x+9=24 | | -9-2x=-(5+4x) | | =100000(1+0.04/360) | | 11=s-3 | | 0=4-28t+49t^2 | | x^2+29xy+100y^2=0 | | -1x+2=5 | | 7*5x=28 | | (27/9x)=x | | -7n+33=-6(n-6) | | x^2-2x-8/2x^2-8x | | -2y-3=8y+67 | | 3h=-15 | | 2g+6=38 | | 5(5k-8)=160 | | -12-2n/3 | | 27/9x=x |